Gambaran Stress Kerja Perawat dalam Pelaksanaan Asuhan Keperawatan pasien HIV/AIDS - Erlina, Rita; Winarso, Mariyono Sedyo; Haryani, Haryani (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2006)
Please refer to the file